2021
DOI: 10.1371/journal.pone.0250719
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated to neural tube defects among mothers who gave birth in North Shoa Zone Hospitals, Amhara Region, Ethiopia 2020: Case control study

Abstract: Introduction Neural tube defects affect the brain and the spinal cord of the developing embryo. The defects occur due to incomplete or failure of closure of the neural tube. The condition eventually causes death and lifelong disability. Worldwide, more than 300,000 babies are born with neural tube defects each year. The highest burden is in low- and middle-income countries. Therefore, this study aims to identify the risk factors associated with neural tube defects among mothers who gave birth in North Shoa Zon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…By reviewing maternal medical records, the study population consisted of all newborns delivered at Debre Berhan Comprehensive Specialized Hospital from June 1, 2019 to June 1, 2021. According to the ICD-10 criteria, NTDs cases include anencephaly, spinal bifida, myelomeningocele, and encephalocele occurring either separately or in combination with other congenital malformations ( 21 ), whereas the controls are newborn babies without NTDs ( 22 ).…”
Section: Methodsmentioning
confidence: 99%
“…By reviewing maternal medical records, the study population consisted of all newborns delivered at Debre Berhan Comprehensive Specialized Hospital from June 1, 2019 to June 1, 2021. According to the ICD-10 criteria, NTDs cases include anencephaly, spinal bifida, myelomeningocele, and encephalocele occurring either separately or in combination with other congenital malformations ( 21 ), whereas the controls are newborn babies without NTDs ( 22 ).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies demonstrated the negative medical side effects caused by an enhanced and indiscriminate use of pesticides ( 69 , 70 ). Several lines of evidence reported that pesticides contribute to significant developmental and reproductive disorders with carcinogenic and teratogenic capabilities ( 69 , 71 , 72 ). Several previous experimental and case reports indicated a connection between congenital disorders and pesticide exposure ( 69 71 , 73 , 74 ).…”
Section: Etiology—neural Tube Defectsmentioning
confidence: 99%
“…Several lines of evidence reported that pesticides contribute to significant developmental and reproductive disorders with carcinogenic and teratogenic capabilities ( 69 , 71 , 72 ). Several previous experimental and case reports indicated a connection between congenital disorders and pesticide exposure ( 69 71 , 73 , 74 ). A study performed in Washington, USA, showed the increased risk of development of neural tube defects post pesticide exposure ( 75 ).…”
Section: Etiology—neural Tube Defectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal obstetric factors associated with increased risk of NTDs mentioned in several studies include; unplanned pregnancy ( 19 , 21 , 22 ), previous history of abortion ( 20 ), previous history of stillbirth ( 15 , 19 , 20 , 23 ), gender of the fetus ( 19 , 21 , 22 ), previously affected child ( 23 - 25 ), family history of NTDs ( 17 ), and multivitamin or folic acid supplementation early in pregnancy ( 19 - 23 ). Smoking and indoor air pollution associated with inadequate housing conditions increase the risk of having a fetus with NTDs ( 18 , 26 ).…”
Section: Introductionmentioning
confidence: 99%